Infective Endocarditis as the Cause of Death: A Population based Study in Portugal, from 2002 to 2018 - de Sousa, Catarina (2021)
Introduction: Infective endocarditis presents a high rate of morbidity and mortality. Population-based studies addressing mortality caused by infective endocarditis in Portugal are scarce. We aimed to study deaths caused by Infective endocarditis, as well as corresponding demographics and temporal trends.Material and Methods: Retrospective cohort study of all patients whose main cause of death was Infective endocarditis in Portugal from 2002 to 2018. The data was obtained from the national death certificate information system.Results: In Portugal, 3634 people died from infective endocarditis throughout the 17-year study period - infective endocarditis specific mortality rate of 2.1 per 100 000 habitants. Of all deceased, 89% were at least 60 years old, and most were women (55%). Overall, 72% died in a healthcare institution. An annual 9% increase in the incidence death rate from Infective endocarditis was observed, with a significant upward trend during the colder months.Discussion: In Portugal, mortality by infective endocarditis increased, mainly affecting older patients and women, and which can partially be explained by factors such as ageing of the population. The management of older patients with infective endocarditis is challenging as they present a higher number of comorbidities, more valvular heart disease and valve implants, invasive medical procedures and are less likely to undergo cardiac surgery.Conclusion: In addition to data on the evolution of demographics in Portugal, it is crucial to study the incidence of infective endocarditis over time to help explain these findings. The identification of factors that can be used to better model national health policies to improve clinical outcomes of infective endocarditis in Portugal is also required.